Structural and Electronic Factors Governing the Action of Anticonvulsants - Lisgarten, John N; Palmer, Rex A (Journal of Drug Delivery and Therapeutics, 2020)
A selection of eighteen anticonvulsant drug molecules has been subjected to both geometrical analysis and atomic charge calculation to search for a link between structure and activity. A significant consequence of this study is the discovery of a fused 5,6,7 chemical ring system which suggests that these drugs may interact with a receptor site which is its topological complement. Molecular orbital calculations support the observation that anticonvulsant activity appears to be related to the net atomic charge on a specific carbon atom which is central to the fused ring system. Keywords: Anticonvulsant, lamotrigine, epilepsy, charge calculation.